The place of peronism in the history of science in Argentina - Hernan Comastri (Ибероамериканские тетради)
This research is part of a larger study aimed at reconstructing the various ways in which professional historiography and other non-academic historical discourses have dealt with the relationship between Science and Peronism in contemporary Argentina. The purpose of this study is to analyze the overly simplistic image of this relationship that still persists in social memory and, to a large extent, continues to influence historical research agendas and the more general political debate. The article provides a bibliographic review and offers a reading key, useful for future research agendas, in which the history of science and that of Peronism intersects, coming from both professional historiography and of the disciplinary histories many times rehearsed by the scientific community itself. These investigations cover a multitude of topics, but for reasons of space and focus, we will focus here mainly on those disciplines that, broadly speaking, we could encompass within the “exact and natural sciences” and engineering. Based on these considerations, it is possible to observe that this field of study still reproduces a set of stereotypes that limit historical knowledge about the period, both with regard to the insertion of Peronism in a long-term reading of state policies in science and technology, as in its insertion in the history of the university in Argentina.